Cardiorespiratory fitness and body composition of soccer referees: Do these correlate with proper performance? - Mazaheri, R.; Halabchi, F.; Barghi, T- S.; Mansournia, M. A. (Asian Journal of Sports Medicine, 2016)
Background: The elite-level referee is exposed to similar physical demands to those placed on a midfield soccer player. They have an important responsibility to implement the rules of the game. So, good health and performance of soccer referees have a great importance.